Literature Review on Requirement Prioritization Methods - Glory Vijayaselvi, K; Thirumalai Selvi, R (International Journal of Computer Sciences and Engineering, 2025)
Requirement Engineering is a very important phase in SDLC. The success and failure of the end product has direct connection with this Requirement Phase. So the output quality of this phase plays a vital role. Requirement Prioritization Process (one of the process) in this phase helps the engineers to work out and find the prioritization among the requirements. Because of the constraints – cost, time and other factors, prioritization plays an imperative role in the development of project and also to improve the goodwill of the company in the competitive market. In this paper, the Requirement Prioritization techniques are discussed and research articles related to the topics are reviewed. Based on the analysis of previous research, the comparisons between the mostly used models are made, drawbacks and strengths are discussed.